VISUALIZATION OF DATA AND RESULTS AS А METHODOLOGICAL BASIS OF APPLIED STATISTICS TEACHING - R. R. Nuriakhmetov (Бюллетень сибирской медицины)
Traditional methods of teaching in medical high school of informatics as computer sciences and statistics as a section of high mathematics contradict to requirements of modern applied medicine and a medical science. A research objective is revealing of the reasons of the given discrepancy and its elimination ways. Similar discrepancy was revealed earlier by foreign researchers studying efficiency of the statistic school programs. The revealed laws appeared to be extended to a technique of teaching of statistics in a high medical school. Pursuing this aim the tests of educational achievements developed by the author were applied on the students of medical and biologic department of the Siberian State Medical Universirty that trained on specialities of “biophysics" and “biochemistry". The fundamental problem of statistical education is that symbols used by these science concern to the objects, which students still have to design. As a substantiation of this conclusion serves the ontosemiotical approach to working out of the maintenance of a course. In the article there are considered the approaches to the permission of the given contradiction, based on the experience of teaching of statistics in foreign schools and on the workings out of the author. In particular the conclusion about necessity of revision the tradition of using professional statistical packages and introduction of a special educational software. To working out the maintenance of a learning course it is offered to more widely apply the historical approach which concrete definition is represented by a principle of a guided reinvention.